2013
DOI: 10.1587/elex.10.20130187
|View full text |Cite
|
Sign up to set email alerts
|

Microelectromechanical XNOR and XOR logic devices

Abstract: Abstract:We have developed a new microelectromechanical logic device using the MEMS (Micro Electro Mechanical Systems) technology. This device consists simply of a single cantilever and two driving electrodes with two contact pads for electrostatic operation. Both exclusive NOR (XNOR) and exclusive OR (XOR) logic devices have been realized using this simple construction. Keywords: logic circuits, space applications, mechanical switch, electrostatic pull-in Classification: Micro-or nano-electromechanical system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In this section, we demonstrate one potential application of the studied device to perform 2-bits logics functions, such as NOR, XOR, and AND, dynamically using the shift in its first mode frequencies. Such devices have been the subject of increasing interest in recent years [32][33][34]. Here, the high motional current of a capacitively sensed resonator is taken as output HIGH at resonance.…”
Section: Application : 2-bit Logic Functionsmentioning
confidence: 99%
“…In this section, we demonstrate one potential application of the studied device to perform 2-bits logics functions, such as NOR, XOR, and AND, dynamically using the shift in its first mode frequencies. Such devices have been the subject of increasing interest in recent years [32][33][34]. Here, the high motional current of a capacitively sensed resonator is taken as output HIGH at resonance.…”
Section: Application : 2-bit Logic Functionsmentioning
confidence: 99%
“…In recent years, researchers have explored microelectrome chanical systems (MEMS) resonators for different applications such as sensors [1][2][3][4], actuators [5][6][7], filters [8][9][10], switches [11][12][13], memory [14][15][16] and logic gates [17][18][19][20]. There has been significant interest in using MEMS resonators par ticularly as digital computing devices due to their run time reprogramability and low energy consumption especially in the off state.…”
Section: Introductionmentioning
confidence: 99%
“…A universal logic gate was demonstrated with multi-bit logic functions using a single parametrically excited resonator in [31]. Mita et al [32] demonstrated XNOR and XOR logic gates based on a single cantilever beam. Mahboob et al [33] reported 2-bit and multi-bit logic operations using a single electromechanical parametric resonator by encoding binary information as different oscillation frequencies.…”
Section: Introductionmentioning
confidence: 99%